Leukaemia inhibitory factor is associated with treatment resistance in oesophageal adenocarcinoma. - Dunne, Margaret; Lynam-Lennon, Niamh; O'Sullivan, Jacintha; Ravi, Narayanasamy (My University, 2018)
Oesophageal cancer is an aggressive disease with a poor 5 year survival rate of <20% of diagnosed patients. Unfortunately, only 20-30% Oesophageal Adenocarinoma (OAC) patients show a beneficial response to neoadjuvant therapy (neoCT). Inflammation influences OAC given the increased risk of cancer development and poor outcome for obese patients where altered secretion of adipokines and cytokines from adipose tissue contributes a pro-tumourigenic environment. We carried out a large proteomics screen of 184 proteins to compare the inflammatory and oncogenic profiles of an isogenic radioresistant in-vitro model of OAC. We found that leukaemia inhibitory factor (LIF), an IL-6 type cytokine, was significantly elevated in radioresistant OAC cells (p=0.007). Furthermore, significantly higher circulating levels of LIF were present in the serum from treatment-naive OAC patients who had a subsequent poor pathological response to neo-adjuvant therapy, (p=0.037). Quantitative PCR analysis revealed expression of LIF receptor (LIFR) may function as a predictive indicator of response to neo-adjuvant chemoradiation therapy in OAC. LIF was demonstrated to be actively secreted from human OAC treatment-naïve biopsies and significantly correlated with the secretion of bFGF, VEGF-A and IL-8 (p<0.05, R=1), (p<0.05, R=0.9429), and (p<0.05, R=1) respectively. Importantly, LIF secretion negatively correlated with tumour infiltrating lymphocytes in pre-treatment OAC patient biopsies, (r=-0.8783, p=0.033). Elevated circulating LIF is a marker of poor response to neo-adjuvant treatment in OAC and secretion of this chemokine from the tumour is tightly linked with pro-tumourigenic mediators including bFGF, VEGF-A and IL-8. Targeting this pathway may be a novel mechanism enhance neoadjuvant treatment responses in OAC.
PUBLISHED
Keywords: LIF; Oesophageal cancer; LIFR; Treatment resistance; Radiation